Perbandingan Struktur Komunitas Mikroartropoda Tanah di Lahan Zona Aktif dan Pasif TPA Jatibarang Semarang - Amelinda, Elda Dheiva; Rahadian, Rully; Hadi, Mochamad (Bioma : Berkala Ilmiah Biologi, 2017)
Microarthropods is one of the important components of soil biology which is abundant and varied. The purpose of this research is to compare the structure of microartropod soil community and to examine the influence of physical-chemical factors of the environment based on the dynamics of abundance of soil microartropods in the active zone and the passive zone of Jatibarang Landfill Landfill Semarang. This research was conducted at Jatibarang Landfill Zone of active zone and passive zone by using purposive sampling method. The results showed that the number of species and the number of microartropods in the active zone was higher than the passive zone. In the active zone found 2240 individual / m2 soil microartropods consisting of 21 species and 17 families, whereas in the passive zone found 480 individual / m2 soil microartropods consisting of 10 species and 9 families. The dominating families in both the active and the passive zones are Sciaridae and Cicadellidae. Environmental factors that affect the diversity of soil microartropods are ground water content, soil porosity, heavy metal content such as Pb, Cu, and Zn; As well as the availability of organic matter in the soil.Â Keyword: Community structure, soil microarthropods, heavy metals, Jatibarang landfill